Faktor-faktor yang Memengaruhi Produktivitas Tenaga Kerja Penyadap PT. Bridgestone Sumatra Rubber Estate Dolok Melangir, Sumatera Utara - DAMANIK, HADI JONTUAHDO; DEWI, RATNA KEMALA; WIDHIANTHINI, WIDHIANTHINI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2023)
Factors Affecting Manpower Productivity Employees Tapping PT. Bridgestone Sumatra Rubber Estate Dolok Melangir. Productivity is a description of the ability of workers to produce output. The higher the output produced by a worker, the higher the productivity of the worker. PT. Bridgestone Sumatera Rubber Estate Dolok Merangir is a company engaged in the plantation and processing of rubber latex that produces high quality products in the form of semi-finished goods called Crumb Rubber or SIR (Standard Indonesian Rubber). However, there are many factors that will affect the productivity of the workforce in the company. Therefore, what will be analyzed in this study is the influence of the motivation level, the work environment, the work experience and work discipline on the productivity of rubber tappers of PT. Bridgestone Sumatera Rubber Estate Dolok Merangir. This study aims to analyze the effect of (1) work motivation variables, (2) work environment, (3) work experience and (4) work discipline on the productivity of PT. Bridgestone Sumatera Rubber Estate Dolok Merangir In this study, primary data was used through direct interviews with 96 respondents from PT. Bridgestone Sumatra Rubber Estate Dolok Merangir with a list of questions that have been prepared. To achieve the goal, in this study using a quantitative description method with SEM-PLS. The results of this study indicate that the variables of work motivation and work environment have a positive and significant effect on work productivity, while work experience and work discipline are not significant on work productivity tapping PT. Bridgestone Sumatera Rubber Estate Dolok Merangir. Suggestions that can be given to the management of PT. Bridgestone Sumatra Rubber Estate Dolok Merangir, North Sumatra is to increase the responsibility of tappers by way of more intensive supervision by the plantation side, providing feedback to the tapping workforce that exceeds the productivity set by the company, and paying attention to the welfare of its employees to increase work productivity.